Investment Analysis of a Lake Water Treatment System into Drinking Water and Design of the Lake Water Management Supply Chain at MAN IC Paser, East Kalimantan - Oviyan Patra; Andy Sugara (International Journal of Marine Engineering Innovation and Research, 2026)
The availability of safe and sustainable drinking water is a vital necessity for boarding educational institutions. Madrasah Aliyah Negeri Insan Cendekia (MAN IC) Paser faces limitations in the quantity and continuity of clean water supply from external providers, while at the same time possessing a potential surface water source in the form of a lake with a large storage volume. However, the quality of the lake water does not yet meet drinking water standards, as indicated by high turbidity levels and potential microbiological contamination. This study aims to analysis of investment of the design a lake water treatment system into drinking water that complies with the Indonesian Ministry of Health Regulation No. 492 of 2010, as well as to design an efficient and sustainable water management supply chain and ecosystem. The research methods include raw water quality analysis, jar test experiments using several types of coagulants, the design of a water treatment plant (WTP) employing a conventional treatment system, and supply chain analysis based on a systems thinking approach. The results show that a complete water treatment system consisting of presedimentation, coagulation–flocculation, sedimentation, filtration, and disinfection is able to reduce turbidity to meet drinking water quality standards. In addition, the integrated supply chain design supports the operational sustainability of drinking water provision within the MAN IC Paser environment. This study is expected to serve as a model for drinking water self-sufficiency based on local resources in educational institutions.